THE ROLE OF AGRICULTURAL EXTENSIONERS AND AGRICULTURAL FARMER CHARACTERISTICS ON THE BEHAVIOR OF RICE SEED FARMERS IN BUNGA RAYA DISTRICT, SIAK REGENCY - Rini Nizar; Hamdan Yasid; Khairunnas Khairunnas; Erick Gunawan Bahar (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Cultivation techniques carried out by paddy farmers in Siak regency are generally still traditional and dominantly use local varieties. one of the efforts to increase production, government through related agencies produce superior rice seeds. This superior rice seed will be effective and have a broad impact if it is adopted by farmers through dissemination and extension methods. This study aims to determine the role of agricultural extension and the characteristics of farmers who carry out superior rice seed farming in Bunga Raya District, Siak Regency. This type of research is survey. the data used in this study are primary data and secondary data. Primary data was taken using a questionnaire.  secondary data was taken from related agencies. The data obtained was analyzed using Structural Equation Modeling (SEM) and then processed using the SmartPLS 3.0 data processing application. Determination of the sample was carried out by purposive random sampling, amounting to 100 people with the criteria of rice farmers who also work as rice seed breeders. Research results showed that farmers' skills are influenced by education, monitoring and evaluation. The attitude of farmers is influenced by education, consultation. Farmer's knowledge is influenced by farmer characteristics, facilitation, monitoring and evaluation. Education, consultation, facilitation, monitoring and evaluation which are dimensions of the role of extension agents significantly influence the behavior of rice seed breeders consisting of knowledge, attitudes and skills.